Unaccompanied foreign minors and mental health: Implementation and evaluation of the RHS-15 screening procedure for unaccompanied foreign minors - Marco Fontana; Francesco Fattori; Sofia Trezzi; Massimo Conte; Laura Bernardini; Laura Marando; Giovanni Michelini; Andrea Trapani; Maria Antonella Costantino (Elsevier, 2023)
Background and objective: The recent notable increase in refugees' flows, with refugee children and adolescents relocating worldwide, posed severe challenges to the different national healthcare systems. Social groups such as refugees fleeing from their countries because of persecution, wars and violence are considered at high risk of developing mental health-related problems. Despite international and national policies legally regulating the reception process and protecting health-related rights, including the mental well-being of refugee migrants, there is a theoretical and applied need for evidence-based instruments and procedures to support mental health within this population. Recent evidence refers to the Refugee Health Screener-15 (RHS-15) as a reliable and valid instrument for the early detection of trauma-related mental health problems. In this scenario, this study aimed to test the RHS screening process within a multidisciplinary first intervention reception context for unaccompanied refugee minors. Design: The RHS-15 was administered with the support of cultural-linguistic mediators to 81 unaccompanied minor residents in a first intervention facility in Milan, Italy. This study aimed to assess psychometric characteristics, such as reliability, sensitivity and specificity feasibility and its implementation within a first intervention reception process. Results: The analysis resulted in the validation of the RHS in its 13-item format. The results highlighted and confirmed an efficient delivery, excellent reliability and a positive predictive and convergent validity of the 13-item version. Further analysis showed an excellent ability to avoid false negatives, although there was a clear tendency to identify false positives. Conclusions: The early identification of vulnerabilities among refugee minors is recommended to promote their long-term overall well-being. Integrating the screening results with additional observational elements and more specific diagnostic tools is recommended to gain a comprehensive perspective of the minors' well-being.